2023
DOI: 10.3390/jpm13020221
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1, CD4+, and CD8+ Tumor-Infiltrating Lymphocytes (TILs) Expression Profiles in Melanoma Tumor Microenvironment Cells

Abstract: (1) Background: Because melanoma is an aggressive tumor with an unfavorable prognosis, we aimed to characterize the PD-L1 expression in melanomas in association with T cell infiltrates because PD-1/PD-L1 blockade represents the target in treating melanoma strategy. (2) Methods: The immunohistochemical manual quantitative methods of PD-L1, CD4, and CD8 TILs were performed in melanoma tumor microenvironment cells. (3) Results: Most of the PD-L1 positive, expressing tumors, have a moderate score of CD4+ TILs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…However, it remains unclear as to which cell would be most suitable to determine a response to anti-PD-1 antibodies. 26 By the same token, presence of increased TILs could also point towards high PD-L1 expression, 2729 as was seen in the present study ( P < .001).…”
Section: Discussionsupporting
confidence: 82%
“…However, it remains unclear as to which cell would be most suitable to determine a response to anti-PD-1 antibodies. 26 By the same token, presence of increased TILs could also point towards high PD-L1 expression, 2729 as was seen in the present study ( P < .001).…”
Section: Discussionsupporting
confidence: 82%
“…Thus, targeting the Wnt/β-catenin signaling pathway in immune cells (e.g., T lymphocyte, NK cells and macrophage) may restore the patient's immunocompetence. Historical studies have shown that melanoma is also one of the most immunomodulatory-sensitive malignancies, and intensive infiltration being correlated to favorable prognosis [ 49 , 50 ]. We speculate that there may be interactions between PDPN and tumor-infiltrating immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 We were particularly drawn to the PD-1/PD-L1 cascade with the well characterized relationship between increased PD-1 expression and suppressed T cell function along with the observation that tumor cells and regulatory/support cells both can express PD-L1 to evade T-cell-mediated antitumor immunity. The presence of PD-L1 is a negative prognostic marker 17,18 with reports of circulating PD-L1 positive monocytes, associated with some cancers. [19][20][21] Hence, we hypothesized that designing PD-L1 targeting CAR T-cells would not only be able to strike tumor cells but would also attack the PD-L1 expressing regulatory/support cells resulting in the destabilization of the cellular network that generates the immunosuppressive TME.…”
Section: Gbm Patient-derived Mc9999 Car T-cells Targeted Primary Gbm ...mentioning
confidence: 99%